2021
DOI: 10.1016/j.ajem.2021.01.051
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of treatment, transport, and refusal incidence in a National EMS's routine work during COVID-19

Abstract: Background: COVID-19 created lifestyle changes, and induced a fear of contagion affecting people's decisions regarding seeking medical assistance. Concern surrounding contagion and the pandemic has been found to affect the number and type of medical emergencies to which Emergency Medical Services (EMS) have responded. Aim: To identify, categorize, and analyze Magen David Adom (MDA), Israel's national EMS, pre-hospital activities including patients' refusal to hospital transport, during the COVID-19 pandemic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…More interestingly, the proportion of non‐pandemic defunct calls rose after the outbreak of the Covid‐19 pandemic. The rise of refusals to transportation to hospitals has also been observed in Israel 57 . This corroborates with earlier studies in the United States suggesting that people showed reluctance to receive hospitalisation out of fear of contagion 13,58…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…More interestingly, the proportion of non‐pandemic defunct calls rose after the outbreak of the Covid‐19 pandemic. The rise of refusals to transportation to hospitals has also been observed in Israel 57 . This corroborates with earlier studies in the United States suggesting that people showed reluctance to receive hospitalisation out of fear of contagion 13,58…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies have found an increase in EMS calls regarding cardiac arrest, 34,57,61 stroke 34 mental health 57 and overdose, 34 during the early stages of the Covid‐19 pandemic. Our study confirmed that, in the long term, the EMS demand for these problems did not decrease.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of transport refusal in the present study was 15.0% ( Table 4 ). The levels of prehospital transport refusal in this study were slightly lower (19.9%) than the results of transport refusal incidents reported from the study conducted in Israel amid the COVID-19 pandemic [ 38 ]. The difference could be explained by the fact that the study from Israel included all medical emergency incidents regardless of the causes while the present study focused on transports of COVID-19 patients alone.…”
Section: Discussioncontrasting
confidence: 77%
“…However, our finding was no more statistically significant after adjusting for potential confounders ( Table 6 ). Transport refusal was previously reported as a predictor of clinical deterioration and adverse outcomes in prehospital care [ 38 ]. Further studies are needed to confirm the association between transfer refusal and adverse events in prehospital care in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…Many different explanations have been proposed: Lifestyle changes brought about by the imposed lockdown may have influenced the propensity to become injured in driving accidents or other recreational activities [ 15 – 19 ]. It is also possible that the fear of contagion of SARS-CoV-2 has reduced the incentive to call for emergency medical assistance [ 6 ]. It has even been reported that patients have refrained from calling on the health care system for fear of “disturbing” the system during the pandemic [ 20 ].…”
Section: Discussionmentioning
confidence: 99%